Valproate-induced disorders of dopamine metabolism and the development of valproate-induced parkinsonism: a new perspective on prevention and diagnosis - N. A. Shnayder; V. V. Grechkina; M. Y. Kissin; R. F. Nasyrova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The problem of valproate-induced adverse drug reactions, including valproate-induced parkinsonism is of high relevance due to the widespread use of valproates in psychiatric and neurological practice and the complexity of the pathogenesis of dopaminergic neurotransmission disorders. Unfortunately, personalized algorithms for practicing physicians based on the use of modern methods of pharmacogenomics and pharmacometabolomics of valproate-induced parkinsonism have not yet been developed. The most important methods of diagnosis and prognosis of valproate-induced parkinsonism are 1) investigation of neurologic status (assessment of motor and non-motor symptoms of drug-induced parkinsonism); 2) therapeutic drug monitoring of total and free fractions of valproic acid; 3) study of the level of toxic metabolic metabolites of valproic acid in blood and urine; pharmacogenetic testing of non-functional single nucleotide variants of genes encoding key metabolic enzymes and key transport proteins of valproic acid efflux across the blood-brain barrier.